Investigations on Growth, Characterization, NCI-RDG, AIM, Molecular Docking and In-Silico ADME Properties of 1,2-Benzene Dicarboxylic Acid Anhydride - Saravana Kumar G.; Jeyalaxmi M.; Vijayanarasimhan K.; Boukabcha N.; Chouaih A. (Orbital: The Electronic Journal of Chemistry, 2024)
Superior single crystal of 1,2-benzene dicarboxylic acid anhydride additionally called Phthalic anhydride (PAN) was developed via solution growth at low temperatures. Single crystal X-ray diffraction investigation revealed the crystal system and unit cell characteristics. The phase stability and crystalline nature were uncovered by powder X-ray diffraction analysis. FT-IR examination was done for the titular material so as to survey the various functional groups. With the use of the VEDA program's relevant resources, vibrational assignments have been made on the concept of Potential Energy Distribution (PED). Density Functional Theory (DFT) was employed to smooth out the molecular structure of PAN and was additionally utilized to consider FT-IR spectrum at molecular level.  Non covalent interactions reduced density gradient (NCI-RDG) analysis has been used for the prediction of the weak interaction in the actual space in terms of the electron density along with its derivatives for PAN. Atoms in Molecules (AIM) analysis was carried for out for PAN. The docking research of the small molecule (PAN) with target protein confirmed that this is a great molecule which docks nicely with numerous targets associated with Hypoxia Inducible Factor 1-α. The absorption, distribution, metabolism, excretion (ADME) characteristics have been calculated with the assist of online server preADMET.